Aproveitamento de resíduo de caulim em cerâmica branca - Souza, Lana Lopes de (2007)
The world market of Kaolin has been growing as new investments for better quality of materials have been applied. This market produces amounts of dross that are put in the environment in a wrong way, causing damages to it. Trying to reduce these damages, researches have been done in an attempt to use kaolin dross in ceramic. The disposal of kaolin dross in the environment by the industries of the states of Rio Grande do Norte and Paraiba have great impact in society. Usually this dross is disposed clandestinely in places like roads, river banks and lands of small cities. The present work shows the characteristics of the kaolin produced by the mining company in Junco do Seridó, Paraiba state, western Seridó, 300 km from Natal, in the border of both states. After that, researches were done to study its physical and the chemistry characteristics, trying to see if it can be used in white ceramic. The samples got were bolted in fabric of 325# . The technological characteristics tried to use it as a product in white ceramic. For that, it was made a haracterization of the subject matter through enlargement analyses, ATG and ATD, elaborating three formulations that were burned in four different temperatures, 1175, 1200, 1250 and 1300 degrees centigrade up to 30 minutes. After the burning, the subjects were submitted to water absorbing tests, linear retreating, apparent porosity, apparent specific mass, resistance to flexibility and MEV. For one of the mixtures it was obtained demanded properties for a semi porous material